![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,=3x\left(y-z\right)-y\left(y-z\right)=\left(3x-y\right)\left(y-z\right)\\ b,=x^3\left(x-1\right)+x\left(x-1\right)=x\left(x^2+1\right)\left(x-1\right)\\ c,=x\left(y+z\right)+y\left(y+z\right)=\left(x+y\right)\left(y+z\right)\\ d,=\left(x-3\right)^2\\ e,=\left(x+2\right)^3\\ f,=\left(2x-x+y\right)\left(2x+x-y\right)=\left(x+y\right)\left(3x-y\right)\\ g,=\left(y+1\right)\left(5x-2\right)\\ h,=\left(x+2\right)^2\\ i,=x^2\left(x^2-2\right)\\ k,=3x\left(x-4y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
do hơi bận nên mk ghi đáp án nha, ko hiểu đâu ib mk
a) \(3xy^2-2xy+12x=x\left(3y^2-2y+12\right)\)
b) \(x^3-10x^2+25x-16xy^2=x\left(x-4y-5\right)\left(x+4y-5\right)\)
c) \(5y^3-10xy^2+5x^2y-20y=5y\left(y-x-2\right)\left(y-x+2\right)\)
d) \(x^2+2xy+y^2-xz-yz=\left(x+y\right)\left(x+y-z\right)\)
e) \(9x^2+y^2+6xy=\left(3x+y\right)^2\)
f) \(8-12x+6x^2-x^3=\left(2-x\right)^3\)
g) \(125x^3-75x^2+15x-1=\left(5x-1\right)^3\)
h) \(x^2-xz-9y^2+3yz=\left(x-3y\right)\left(x+3y-z\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x3 + 8y3) : (2y + x)
= (x + 2y)(x2 - 2xy + 4y2) : (2y + x)
= x2 - 2xy + 4y2
b) (x3 + 3x2y + 3xy2 + y3) : (2x + 2y)
= (x + y)3 : 2(x + y)
= \(\dfrac{\left(x+y\right)^2}{2}\)
c) (6x5y2 - 9x4y3 + 15x3y4) : 3x3y2
= 3x3y2(2x2 - 3xy + 5y2) : 3x3y2
= 2x2 - 3xy + 5y2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(9x^2-12x+4=\left(3x-2\right)^2\)
b) \(25+10x+x^2=\left(x+5\right)^2\)
c) \(36x^2-25=\left(6x-5\right)\left(6x+5\right)\)
d) \(x^3-3x^2y+3xy^2-y^3=\left(x-y\right)^3\)
a: \(9x^2-12x+4=\left(3x-2\right)^2\)
b: \(x^2+10x+25=\left(x+5\right)^2\)
c: \(36x^2-25=\left(6x-5\right)\left(6x+5\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(10x\left(x-y\right)-6y\left(y-x\right)\)
\(=10x\left(x-y\right)+6x\left(x-y\right)\)
\(=\left(10x+6x\right)\left(x-y\right)\)
\(c,3x^2+5y-3xy-5x\)
\(=\left(3x^2-3xy\right)+\left(5y-5x\right)\)
\(=3x\left(x-y\right)-5\left(x-y\right)\)
\(=\left(3x-5\right)\left(x-y\right)\)
\(e,27+27x+9x^2=3\left(9+9x+x^2\right)\)
\(\left(12x^2y^3-15x^4y^3+9x^2y^2\right):3xy^2\)
\(=4xy-5x^3y+3x\)